Profitability Ratio Analysis to Measure Financial Performance at PT. Bank Sulselbar Makassar Main Branch - Haeruni Rezky Kanna; Zainal Ruma; Anwar; Romansyah Sahabuddin; Nurman (Lafadz Jaya Publisher, 2023)
Financial performance plays an important role as a description of the company's ability to manage existing resources. Profitability ratios can be used as a tool to measure the company's financial performance in determining the company's efficiency in managing assets to obtain the maximum level of profit. This study aims to determine the financial performance of PT Bank Sulselbar Makassar Main Branch in the 2018-2022 period. The variables of this study are profitability ratios and financial performance. The population and sample of this study were financial statements in the form of balance sheets and profit and loss from PT Bank Sulselbar Makassar Main Branch in 2018-2022. Data collection was carried out using documentation techniques. Data analysis was carried out using profitability ratios with the two pont system approach. The results of this study indicate that the ROA ratio level of PT Bank Sulselbar Makassar Main Branch for the period 2018-2022 is classified as very healthy and the ROE ratio level of PT Bank Sulselbar Makassar Main Branch for the period 2018-2022 is classified as healthy. This is influenced by fluctuations in net income.